Application of typeface design on preschooler's reading materials - Jong, Wan Sia (Universiti Malaysia Sarawak (UNIMAS), 2014)
Typography is an important visual aspect of communication in the learning process. This study focused on the use of typeface suitable for pre-school children between the ages of three of five years. The objectives of the study is to identify the importance of typeface among preschoolers. The findings of this study will improve the skills of children in recognizing the alphabet. Proposed final year project is a revival in graphic design and visual elements of typography to help the learning process among proschoolers.